2010
DOI: 10.1071/bt09188
|View full text |Cite
|
Sign up to set email alerts
|

Cytological analysis of hybrid embryos of intergeneric crosses between Salix viminalis and Populus species

Abstract: Intergeneric hybridisation between Salix viminalis L. as the female and four Populus species (Populus trichocarpa, P. tremula, P. × canadensis and P. simonii) as male pollen donors was performed by in vitro stigma pollination. To overcome postzygotic barriers, transfer of hybrid embryos to new medium is necessary. We carried out detailed ultrastructural analyses to establish: (i) at which stage of embryo development the first signs of programmed cell death (PCD) could be detected; and (ii) at which stage the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In this case, mega‐autophagy plays a role in cell death and the recycling of cell material, suggesting that other types of autophagy could occur in developmental PCD. Cytological observations of degenerating intergeneric embryos (Bagniewska‐Zadworna et al, 2010) revealed that different types of autophagy occurred at the same time, although two different types of vacuolization of embryo cells were noticed, resulting in different modes of PCD.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, mega‐autophagy plays a role in cell death and the recycling of cell material, suggesting that other types of autophagy could occur in developmental PCD. Cytological observations of degenerating intergeneric embryos (Bagniewska‐Zadworna et al, 2010) revealed that different types of autophagy occurred at the same time, although two different types of vacuolization of embryo cells were noticed, resulting in different modes of PCD.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that germination occurred despite the limited contact of Populus pollen with Salix papillae, although the frequency of fertilization was rather low [9,10]. It is apparent that the consequence of the micro-incompatibility of both structures was a slow germination and a greater pollen tube attrition exhibited by poplar pollen.…”
Section: Discussionmentioning
confidence: 98%
“…Breeding of willows involves interspecific hybridization or selection of natural hybrids [5][6][7][8]. Some research on willows has already been carried out in Poland to increase the degree of genetic variability within the species [9][10][11][12]. However, some aspects of the flowering biology and stigma receptivity in Salix are still insufficiently recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of these attempts was to introgress the genes of poplar, the genus with large biomass increments, into the genome of the fast-growing short rotation willow, and are therefore important from the point of view of sustainable energy economy [93][94][95][96][97]. Intergeneric hybridization has also been used to improve other species grown for their rapid biomass accumulation, such as Miscanthus ×giganteus [98][99][100].…”
Section: Culture Of Zygotic and Hybrid Embryosmentioning
confidence: 99%